A Targeted Approach to Improve Asthma Control Using Community Pharmacists - Serhal, Sarah; Saini, Bandana; Bosnic-Anticevich, Sinthia; Krass, Ines; Emmerton, Lynne; Bereznicki, Bonnie; Bereznicki, Luke; Mitchell, Bernadette; Wilson, Frances; Wright, Bronwen; Wilson, Kiara; Weier, Naomi; et al. (Frontiers in Pharmacology, 2021)
Background: Building on lessons learnt from evidence-based community pharmacy asthma management models, a streamlined and technology supported Pharmacy Asthma Service (PAS) was developed to promote the integration of the service into routine practice. Objective: This study investigates the efficacy of the PAS in improving asthma symptom control and other health outcomes. Methods: A two-arm pragmatic cluster randomized controlled trial was implemented in 95 pharmacies across three Australian States. Participants were adults with poorly controlled asthma, with or without allergic rhinitis. Patients within the PAS arm engaged in four consultations with the pharmacist over a 12-month period. An evidence-based algorithm guided pharmacies, via a trial specific software, to deliver a series of interventions targeting three issues underpinning uncontrolled asthma (medication use and adherence, inhaler technique, and allergic rhinitis management) to patient clinical asthma status and patient need. Comparator arm patients received a minimal intervention likened to usual practice involving referral of eligible patients to the GP and two follow-up consultations with their pharmacist to collect comparative data. Results: In total, 143 of 221 PAS patients (65%) and 111 of 160 comparator patients (69%) completed the trial. Improvements in asthma control were achieved in both the PAS (mean difference in ACQ from baseline =-1.10, p<.0001) and comparator (mean difference in ACQ from baseline =-0.94, p<.0001) arms at the trial end; however, there were no significant differences between the two arms (mean difference = -0.16, 95% CI -0.41 to 0.08, p=0.19). Patients’ quality of life in the PAS arm improved significantly when compared with the comparator arm (mean difference in IAQLQ=-0.52, 95% CI -0.89 to -0.14, p=0.0079). Conclusions: Despite the PAS achieving a greater improvement in patients’ quality of life, the pharmacist-led service and usual practice arm produced comparable improvements in asthma control. These results ask us to reflect on current standards of usual care, as it appears the standard of asthma care in usual practice has evolved beyond what is reported in the literature.